Effects of probiotic litchi juice on immunomodulatory function and gut microbiota in mice. (November 2020) - Wen, Jing; Ma, Lan; Xu, Yujuan; wu, Jijun; Yu, Yuanshan; Peng, Jian; Tang, Daobang; Zou, Bo; Li, Lu
Graphical abstract: Probiotic litchi juice has the function of improving immune regulation and reshaping gut microbiota composition. Highlights: This is the first report about the effects of FL on immunomodulatory function and gut microbiota in mice. The probiotic abilities of FL were dramatically increased after fermentation with L . casei . FL significantly helped mice to prevent the decrease of immunity. FL could protect the intestinal tract and ameliorate gut microbiota composition of mice. Abstract: Development new functional foods containing probiotics had gained much attention during the past two decades. In this study, probiotic litchi juice was developed, and its effects on immunomodulatory function and gut microbiota were evaluated. Firstly, the litchi juice was fermented with Lactobacillus casei, which increased total phenolic, total flavone, and exopolysaccharide contents of the litchi juice. Hence, the immunomodulatory influence of fermented litchi juice (FL) was investigated in cyclophosphamide-induced mice. The results showed that FL enhanced immune organs indexes (spleen, thymus) and antioxidant capacity, improved the secretions of cytokines (IL-2, IL-6) and immunoglobulins (IgA, IgG, SIgA), and protected the intestinal tract. Finally, the effect of FL on gut microbiota was analyzed by high-throughput sequencing analysis. The changes in the relative abundance of dominant microbe were investigated at phylum and genus levels, respectively. After treatment with FL, the relative abundance of Firmicutes phylum was dramatically increased, as well as the genera of Faecalibaculum, Lactobacillus, and Akkermansia . These findings indicated that probiotic litchi juice could alleviate immune dysfunction and modify gut microbiota structure of mice, which provide a potential functional food to improve the host health.